The therapeutic potential of Gua Sha on fascia: evidence and possible mechanisms - Wang, Beibei; Chen, Hongxiu; Eungpinichpong, Wichai (Intelektual Pustaka Media Utama, 2025)
In recent years, the effects of Gua Sha on fascia have gradually attracted attention. This review evaluates the effects of Gua Sha on fascia and its underlying mechanisms. We searched major academic databases for relevant studies using the keywords